Makna Simbolik Penoi dalam Tari Kejai Suku Rejang di Kabupaten Lebong - Muhammad Akram; Yayah Chanafiah; Sarwit Sarwono (Jurnal Korpus, 2026)
The aim of this research is to determine the relationship between the kejai dance and the Penoi and to find out the symbolic meaning of the Penoi in the kejai dance of the Rejang tribe in Lebong Regency. The method used in this research is qualitative research with an ethnographic approach. Data collection techniques used in this research are: (1) observation, (2) interviews, and (3) documentation. There are 4 research results, namely a general description of the rejang community in Lebong district, the history of Penoi, Penoi in the kejai dance, and the symbolic meaning contained in Penoi. The results of the research state that the Penoi that existed in acient times were different from the Penoi that exist today. The Penoi, which used to look like a room or warehouse as a place for donations, has now turned into a box or device as a requirement for the performance of the kejai dance. Penoi and kejai dance are one unit and are interconnected. The penoi and the kejai dance functions as a separator or divider between male dancers and female dancers before the start of the dance. The elements contained in Penoi all have their own meaning, for example, the golden banana was chosen because people considered it to have high value according to its color, namely gold. Like wise with other elements, all of which have meaning. All the elements in the Penoi are used as symbols of the prosperity of the Rejang tribe.